2012
DOI: 10.1080/02699931.2011.555474
|View full text |Cite
|
Sign up to set email alerts
|

Dampening of positive affect prospectively predicts depressive symptoms in non-clinical samples

Abstract: Past research has convincingly shown that a ruminative response style to negative affect (NA) predicts concurrent and prospective levels of depressive symptoms. Recent findings suggest that how people respond to positive affect (PA) might also be involved in the development of depressive symptoms, although this has heretofore not been tested prospectively. Participants from two non-clinical samples (total N=487) completed measures of depressive symptoms, response styles to NA (negative rumination) and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
106
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 18 publications
(32 reference statements)
22
106
1
2
Order By: Relevance
“…For example, depressed individuals reported a greater tendency to dampen positive emotion than their never-depressed counterparts, but they did not significantly differ from recovered depressed individuals (Werner-Seidler et al, 2013). Moreover, increased dampening of positive emotions predicted depressive symptoms up to 5 months later (Raes et al, 2012). According to this view, the absence of an improvement in positive emotions could be seen as a 'stigmate' or a 'scar effect' (Gorwood et al, 2008(Gorwood et al, , 2014 of past depressive episodes, a factor known to be associated with worse outcome.…”
Section: Discussionmentioning
confidence: 97%
“…For example, depressed individuals reported a greater tendency to dampen positive emotion than their never-depressed counterparts, but they did not significantly differ from recovered depressed individuals (Werner-Seidler et al, 2013). Moreover, increased dampening of positive emotions predicted depressive symptoms up to 5 months later (Raes et al, 2012). According to this view, the absence of an improvement in positive emotions could be seen as a 'stigmate' or a 'scar effect' (Gorwood et al, 2008(Gorwood et al, , 2014 of past depressive episodes, a factor known to be associated with worse outcome.…”
Section: Discussionmentioning
confidence: 97%
“…Dampening is maladaptive in that it renders people less or incapable of fully enjoying or benefiting from positive experiences, but its association with depression is far less well documented as depression research has only recently been directed to positive affect regulation. Still, there are preliminary findings suggesting that a dampening response style to positive affect goes hand in hand with depressive symptoms (e.g., Raes et al 2009Raes et al , 2012Nelis et al 2013;Werner-Seidler et al 2013) and that it may even predict prospective levels of depression .…”
Section: Discussionmentioning
confidence: 99%
“…The authors highlight the importance of not only encouraging patients to participate in enjoyable situations but actually practicing allowing one to feel pleasant emotions. Raes et al [25] found that dampening positive affect predicts depressive symptoms and is also related to symptoms of panic disorder, social phobia, generalized anxiety disorder and OCD [26]. Weeks et al [27][28][29] found that some socially phobic people are fearful of positive evaluations as well as negative evaluation.…”
Section: Positive Emotionsmentioning
confidence: 99%